Pengembangan Media Smart Box pada Materi Aku Patuh Peraturan untuk Siswa Kelas I UPT SD Negeri 253 Gresik - Dwi Rahmawati; Iqnatia Alfiansyah; Afakhrul Masub Bakhtiar (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to (1) describe the development process of the Smart Box I Obey the Rules media; (2) describe the validity of the Smart Box I Obey the Rules media; and (3) describe student responses to the Smart Box I Obey the Rules media. This study uses the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. This research was conducted at the UPT SD Negeri 253 Gresik during the odd semester. The subjects were 25 students, 10 boys and 15 girls. Data collection techniques used included interviews, media expert validation questionnaires, material validation questionnaires, and student response questionnaires. The results of the study indicate that the Smart Box media I Obey the Rules achieved a validation result of 96,25% from media experts, categorized as very valid, a validation result of 98,75% from material experts, and a student response result of 96,8%, categorized as very good. Based on these results, the Smart Box learning media I Obey the Rules is declared valid and pravtical, making it suitable for use as a learning medium for Pancasila Rducation for first-grade elementary school students.